Hordenine Protects Against Lipopolysaccharide-Induced Acute Lung Injury by Inhibiting Inflammation - Zhang, Xiyue; Du, Li; Zhang, Jinrong; Li, Chunyan; Zhang, Jie; Lv, Xuejiao (Frontiers in Pharmacology, 2021)
Acute lung injury (ALI) is a respiratory disease that leads to death in severe cases. Hordenine (Hor), a barley-derived natural product, has various biological activities, including anti-inflammatory and anti-oxidation activities. We investigated the effect of Hor on lipopolysaccharide-induced ALI and its potential mechanism. The anti-inflammatory effects of Hor were detected using in vivo and in vitro models by enzyme-linked immunosorbent assay, real-time polymerase chain reaction, western blotting, and molecular docking simulations. Hor inhibited increases in the levels of inflammatory factors both in vivo and in vitro, and its anti-inflammatory effect inhibited activation of protein kinase B/nuclear factor-κB and mitogen-activated protein kinase signaling. Hor alleviated lipopolysaccharide-induced ALI by inhibiting inflammatory cytokine increases in vivo and in vitro and shows potential for preventing inflammatory disease.